ETC-1002 Attenuates Porphyromonas gingivalis Lipopolysaccharide-Induced Inflammation in RAW264.7 Cells via the AMPK/NF-κB Pathway and Exerts Ameliorative Effects in Experimental Periodontitis in Mice. (16th March 2022) - Li, Hongyan; Zhang, Peipei; Lin, Hongbing; Gao, Huan; Yin, Jianyuan
Abstract : Background . Clinically, the failure of periodontal therapy stems largely from an inability to control the inflammatory response. Resolution of inflammation is an active, energy-requiring repair process, not merely a passive termination of inflammation. AMP-activated protein kinase (AMPK), a key energy sensor, has been shown to negatively regulate inflammatory signaling pathways. Thus, there is a crucial need for new therapeutic strategies to modulate AMPK and to promote enhanced resolution of inflammation. This study is aimed at investigating the anti-inflammatory effects of ETC-1002 through modulating AMPK in periodontitis. Methods . RAW264.7 cells were infected with Pg -LPS in the presence or absence of ETC-1002, following which the expression levels of proinflammatory cytokines and inflammation signaling-related proteins were evaluated by real-time reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting. ETC-1002 was applied in a murine model of periodontitis to determine its anti-inflammatory effect in vivo . Histological changes were investigated by hematoxylin and eosin (H&E) staining, the levels of proinflammatory cytokines were detected using immunohistochemistry, and alveolar bone height was measured using micro-CT imaging. Results . ETC-1002 inhibited the production of proinflammatory cytokines, promoted AMPK phosphorylation, and decreased I κ B α and NF- κ B p65 phosphorylation levels in Pg -LPS-treated RAW264.7 macrophages. The inhibitory effects of ETC-1002 on the production of proinflammatory mediators were significantly abrogated by siRNA-mediated silencing of AMPK α in RAW264.7 cells. In vivo, ETC-1002 inhibited inflammatory cell infiltration, the expression of proinflammatory cytokines, and the inflammation-mediated destruction of alveolar bone in mice with experimental periodontitis. The anti-inflammatory effect of ETC-1002 in the periodontium could be reversed by the administration of Compound C, an AMPK inhibitor. Conclusions . ETC-1002 exerts anti-inflammatory effects in Pg -LPS-treated RAW264.7 cells via the AMPK/NF- κ B pathway in vitro and inhibits the progress of experimental periodontitis in mice in an AMPK signaling-dependent manner in vivo . These results provide evidence for the beneficial effects of ETC-1002 in the treatment of periodontitis.